Criteria For Evaluating Proposed Frameworks of A “General Theory of Management” - Massie, Joseph L. (Academy of Management Journal, 1958)
Focuses on the criteria which would be useful in evaluating any proposed framework of a general management theory. Other areas of study that contribute to a general framework of management theory; Relationship of the framework within the framework.